The Future of Central Bank Digital Currencies (CBDCs): Implications for Monetary Policy - Suripah Suripah; Finarsih Septria; Afriani Pravitasari; Murniyati Murniyati (Pusat Riset dan Inovasi Nasional, 2025)
This study investigates the implications of Central Bank Digital Currency (CBDC) implementation and fintech adoption on the effectiveness of monetary policy, emphasizing the mediating role of financial system stability and the moderating influence of public trust in central banks. The research addresses a pressing issue in the digital transformation of global finance: whether digital currencies issued by central banks can enhance policy responsiveness in increasingly cashless and decentralized economies. Using an exploratory qualitative method, this study integrates a systematic review of post 2020 academic literature and central bank reports from The Bahamas, Nigeria, and China. A conceptual framework is developed to examine causal relationships among CBDC design, fintech integration, institutional trust, and policy effectiveness. The findings reveal that CBDC impact is highly context dependent; programmable and inclusive designs, such as China’s Digital Yuan, significantly enhance monetary transmission, whereas technical and social barriers, such as in Nigeria, limit policy effectiveness. The Bahamas serves as an intermediate case where offline and identity linked digital currency supports inclusion and moderate policy gains. The analysis confirms that financial stability mediates the relationship between digital innovation and policy outcomes, while public trust either strengthens or diminishes policy reach. This research contributes to the understanding of CBDC as a policy tool by highlighting institutional, technological, and behavioral factors that determine its success. Implications suggest that policymakers must adopt a multidimensional approach that combines digital infrastructure readiness with strong governance and trust building measures.